MODERN APPROACHES TO IMPROVING THE ECONOMIC EFFICIENCY OF METALLURGICAL ENTERPRISES IN UZBEKISTAN BASED ON INTERNATIONAL EXPERIENCE (International Congress on Economics, Management and Business Studies, 2026)
This study examines modern approaches to improving the economic efficiency of metallurgical enterprises in the Republic of Uzbekistan based on international industrial practices. Particular attention is paid to the problems of high energy intensity, inefficient use of production resources, and insufficient digitalization of metallurgical enterprises. The study analyzes international experience and substantiates promising directions for industrial modernization and sustainable development.
Keywords: metallurgy, economic efficiency, industrial modernization, resource management, digitalization, Uzbekistan